PENENTUAN PERMINTAAN OBAT BERDASARKAN FREKUENSI KONSUMSI DAN KARAKTERISTIK PASIEN DI POSKESDES BLANG POROH MENGGUNAKAN METODE MOORA DAN ARAS - Nurfadillah, Nurfadillah; Humaira, Risa (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Effective drug demand management is essential to ensure availability and continuity of healthcare services, especially at primary healthcare facilities such as POSKESDES. This study aims to design a drug demand decision system based on consumption frequency and patient characteristics using the Multiple Objective Optimization on the basis of Ratio Analysis (MOORA) and Additive Ratio Assessment (ARAS) methods. The system was developed as a decision support tool for healthcare workers to determine drug supply priorities. The research was conducted at POSKESDES Blang Poroh, with data including drug consumption history, patient age, gender, and disease types. The system development process used the waterfall model with PHP programming language and MySQL as the database. The test results show that the system can accurately generate drug demand priorities in accordance with real field conditions. This system is expected to support pharmaceutical logistics efficiency at the basic service level.